Species identification and seasonal prevalence of house dust mites in Assiut City, Egypt: A descriptive study in an urban area - Radwa Ibrahim; Hanan Eldeek; Hussien Rezk; Ragaa Othman; Azza El-Tayeb; Magda Elnazer (Persian Journal of Acarology)
Our study aimed to identify and characterize the common species of house dust mites collected from different areas in Assiut city, study their seasonal variation, and effects of some housing criteria on their prevalence. This could help in the assessment of the magnitude of the current situation in this locality and assist in implementing appropriate investigations and diagnostic tools which in turn offers a better quality of life to allergy sufferers in our study locality as well as for others. Dust samples were collected from eight regions representing the two main districts of Assiut City as systemic random samples. For proper dust collection we used both a vacuum cleaner and a hand sweeper from different rooms of each house (bedrooms, mattresses, floor, bedding and living rooms). Also, two methods were used for mite extraction: Kero-float method and modified Berlese-Tullgren funnel. Light microscopy as well as SEM were used to identify different mite species with the aid of an identification key. The overall prevalence of house dust mites in collected samples was 94 positive samples per 300 houses examined in this study. Seasonal variations significantly affected the prevalence of house dust mites; the highest frequency was noticed during winter (66.7%) and the least frequency was noticed during summer (13.3%). Kero-float method was more sensitive and accurate than modified Berlese-Tullgren funnel in mites' extraction in a given sample (100% and 47.9% respectively). The most frequently isolated species were Dermatophagoides farinae (80.9%) and D. pteronyssinus (58.5%) followed by stored products mite, Tyrophagus putrescentiae (50%) and predatory mite, Cheyletus malaccensis (31.9%) while the least frequent species was Dermanyssus gallinae (21.3%). Mixed species were detected in 48 (51.1%) of the positive samples. Some housing criteria: age of the house, damp or moldy stains on floor or on other indoor surfaces (walls, ceiling), presence of carpets/rugs and aeration style (sunny/shady) have significantly affected the prevalence of house dust mites in different houses. We concluded that although Assiut is the driest city in Egypt with low relative humidity, which is an essential factor in the survival of mites, there is significant prevalence of house dust mites (31.3%). Housing criteria significantly affected the presence of HDMs.